Antimicrobial efficacy of thyme essential oil (Thymus vulgaris) on a Staphylococcus aureus strain - Montero Recalde, Mayra (2018)
The objective of this study was to evaluate the in vitro antimicrobial efficacy of thyme essential oil (Thymus vulgaris) on Staphylococcus aureus. Concentrations at 1, 5, 10, 30, 50, 70 and 90% were evaluated in 96.8% dilution in ethanol. The Minimum Inhibitory Concentration was determined by the broth microdilution method. The bacterial inoculum was standardized to 0.5 of the MacFarland scale in spectrophotometer, with the result that the 1% tube of thyme oil did not present turbidity. This, when cultured on Mueller-Hinton agar, determined the Minimum Bactericidal Concentration where no colony growth was observed. The results indicate that treatments at 5 and 10% were not significantly different (p<0.05) with values of inhibition halos of 15.35 mm and 15.9 mm, respetively compared to 1% concentration that presented 12.2 mm of halo of inhibition.